THE EVOLVING RELATIONSHIP BETWEEN ISLAMIC PHILANTHROPY AND ISLAMIC FINANCE: A CONTEMPORARY LITERATURE REVIEW - AINUL IKHSAN; MUHAMMAD DENI PUTRA; RAZALI RAZALI; SURURI SURURI; AGUS KUNTORO (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study explores the relationship between Islamic philanthropy and Sharia-compliant finance by examining how their integration shapes contemporary Islamic social finance. Using a qualitative literature review, the research synthesizes recent studies on productive waqf, digital zakat, and Islamic crowdfunding. The findings show that the success of these innovations depends not only on financial design but also on alignment with socio-cultural norms, religious values, and community trust. Strong religiosity, supportive cultural traditions, and credible governance encourage public participation, while low transparency and weak technological infrastructure remain key challenges. The study highlights the importance of institutional readiness—especially regulation, digital systems, and human capacity—in strengthening integration. It also shows that technology, when guided by Sharia principles, can enhance transparency and financial inclusion. While conceptually comprehensive, the study calls for empirical research to validate these insights.